The Effect of Corporate Governance on Earnings Management in Indonesian Rural Banks - Tri Hanani; Sri Pancawati Martiningsih; Reny Wardiningsih; Novia Rizki; Wulandari Agustiningsih; Deni Karunia Firdausi (Jurnal RAK (Riset Akuntansi Keuangan), 2025)
Earnings are one of the most important measures of company performance. Because of this, many earnings managements are carried out by companies in various sectors, one of which is in the banking sector. The aim of this study is to investigate the impact of corporate governance implementation on earnings management in Indonesian Rural Banks (BPR). This study uses secondary data sources extracted from financial reports and rural banks governance reports from the 2020 to 2023 period, which were collected manually. A total of 44 observations from 11 rural banks were analyzed using panel data regression using the Stata application. Data were also analyzed using descriptive statistics, R-squared, and t-test. The results of this study found that corporate governance has no significant impact on the level of earnings management in Indonesian rural banks. The paper offers evidence of corporate governance failure at the rural bank level in Indonesia. This contributes to the governance and banking risk management science, where it turns out that governance can fail, so that continuous evaluation and monitoring are needed.